The skeptics guide to the global AIDS crisis : tough questions, direct answers - Bourke, Dale Hanson (Atlanta, Ga. : Authentic Media, 2006)
AIDS is the biggest public health problem the world has ever faced. Yet with all the available information, many of us know little about it. There are thousands of books, websites, and professional documents about AIDS, but it takes time to search them to find the simple facts and information that dispel the myths about this pandemic.
The basics -- Health issues -- Economic impact -- Culture and practice -- Laws and politics -- What can be done?
Includes bibliographical references (pages 101-102).
Keywords: AIDS (Disease) -- Epidemiology -- Handbooks, manuals, etc; AIDS (Disease) -- Handbooks, manuals, etc; World health -- Handbooks, manuals, etc; Handbook; Handbooks and manuals; Handbooks and manuals; Guides et manuels